ChemInform Abstract: Palladium‐Catalyzed Regioselective Benzylation—Annulation of Pyridine N‐Oxides with Toluene Derivatives via Multiple C—H Bond Activations: Benzylation versus Arylation. Issue 26 (June 2015) - Kianmehr, Ebrahim; Faghih, Nasser; Khan, Khalid Mohammed
Abstract Conditions for the palladium‐catalyzed 2‐arylation vs.